Bought deals: The value of underwriter certification in seasoned equity offerings - Ari Pandes, J. (Journal of Banking & Finance, 2010)
The bought deal is the predominant method of underwriting SEOs in Canada. Offer prices are set and underwriters commit to purchase offerings several days earlier for bought deals than for firm commitment issues, implying stronger underwriter certification for bought deal issues. Consistent with the certification hypothesis, this study finds a significantly smaller negative stock price reaction around the announcement of bought deals compared to firm commitment issues. Bought deals are further shown to have smaller offer price discounts and smaller underwriting fees, implying superior pricing and thus, higher quality offerings. These findings suggest that investment banks’ underwriting method of choice is informative of issue quality.